2012
DOI: 10.1262/jrd.2012-064
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Vitamin E Improve the <i>In Vitro</i> Maturation, Fertilization and Culture to Blastocyst of Porcine Oocytes

Abstract: Abstract. Selenium (Se) and vitamin E (Vit-E), as integral parts of antioxidant systems, play important roles for sperm and embryos in vitro. In this study, the effects of Se and Vit-E on the maturation, in vitro fertilization and culture to blastocysts of porcine oocytes and accumulation of ammonia in the culture medium during different development stages were investigated. The maturation was performed in modified tissue culture medium (mTCM)-199 supplemented with 10% (v/v) porcine follicular fluid, the ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 63 publications
3
25
0
2
Order By: Relevance
“…The incorporation and oxidation of glucose serve as indicators of the vitality of oocytes and the resulting eggs (Tsujii et al, 2009). In this study, the incorporation and oxidation rates of 14 C(U)-glucose were significantly higher in AlaGln+GlyGln treated oocytes than in the control group during maturation, fertilization, and the 2-cell and blastocyst stages, which was in agreement with the results of our previous study (Tareq et al, 2012). We reported that the combination of selenium and vitamin E in comparison with single supplementation improves porcine embryos, which suggests that the incorporation and oxidation rates of 14 C(U)-glucose were higher in embryos treated with SeMet and SeMet+Vitamin-E at the 2-cell and blastocyst stages.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The incorporation and oxidation of glucose serve as indicators of the vitality of oocytes and the resulting eggs (Tsujii et al, 2009). In this study, the incorporation and oxidation rates of 14 C(U)-glucose were significantly higher in AlaGln+GlyGln treated oocytes than in the control group during maturation, fertilization, and the 2-cell and blastocyst stages, which was in agreement with the results of our previous study (Tareq et al, 2012). We reported that the combination of selenium and vitamin E in comparison with single supplementation improves porcine embryos, which suggests that the incorporation and oxidation rates of 14 C(U)-glucose were higher in embryos treated with SeMet and SeMet+Vitamin-E at the 2-cell and blastocyst stages.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that Gln could be replaced with L-alanyl-L-glutamine (AlnGln) and L-glycyl-L-glutamine (GlyGln) to achieve an increased level of embryonic deployment in mice (Biggers, 2004). We previously reported that the accumulation of ammonia in the medium could be reduced by supplementation with seleon L-methionine (SeMet) and SeMet+Vitamin-E (Tareq et al, 2012). Dipeptides play an important role in oocyte maturation (Tareq et al, 2007) and the porcine sperm acrosome reaction (Tareq et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Proportion of TE cells in porcine IVP blastocysts, compared to in vivo blastocysts, are approximately 46% and 60%, respectively, [27, 28]. Thus, many researchers have attempted to reduce oxidative stress levels by adding numerous supplements with ROS scavenging activity, such as anthocyanin [29], L-carnitine [30], hypotaurine [31], vitamin C [32], β-mercaptoethanol [33, 34] and selenium [35]. Although the effects of FBS supplementation on early development of mammalian IVP embryos have been reported, to our knowledge, no evidence has been published regarding the relationship between FBS and oxidative stress during the early development of mammalian embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies have been performed to reduce ROS using antioxidant treatments such as anthocyanin [18], L-carnitine [19], hypotaurine [20], vitamin C [21], β-mercaptoethanol [22, 23] and Selenium [24]. 7,8-Dihydroxyflavone (7,8-DHF), a kind of flavonoid (Fig.…”
mentioning
confidence: 99%